Students’ responses to teacher’s requests in ’CraftEng’ - Gál, József; Vanderstein, Noémi (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In our running world, Teaching English as a Foreign Language for beginners is a crucial point of education. To motivate young learners is essential in life-long-leaming so it is important to find the best way of introducing foreign languages for children. The teachers have a number of methods and approaches in their hands to choose from in order to produce as many effective language users as possible. During the lessons - next to questions -, teachers use commands and requests to get the students to respond and to react to them. What is more, creative activities and games are popular among students. Schools work by different tactics to invite more and more learners to acquire second language in their institutions. ’CraftEng’ is one of the new trends.